2014
DOI: 10.1371/journal.pone.0114866
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital and One-Year Mortality and Their Predictors in Patients Hospitalized for First-Ever Chronic Obstructive Pulmonary Disease Exacerbations: A Nationwide Population-Based Study

Abstract: IntroductionNatural history of chronic obstructive pulmonary disease (COPD) is punctuated by exacerbations; however, little is known about prognosis of the first-ever COPD exacerbation and variables predicting its outcomes.Materials and MethodsA population-based cohort study among COPD patients with their first-ever exacerbations requiring hospitalizations was conducted. Main outcomes were in-hospital mortality and one-year mortality after discharge. Demographics, comorbidities, medications and in-hospital eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 45 publications
6
66
1
2
Order By: Relevance
“…This study confirms age as a risk factor for one-year mortality as shown by other authors (Connors et al, 1996; Almagro et al, 2002; Groenewegen, Schols & Wouters, 2003; Kim, Clark & Camargo, 2006; Piquet et al, 2013; Ho et al, 2014). Male gender is also associated with increased mortality, although not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirms age as a risk factor for one-year mortality as shown by other authors (Connors et al, 1996; Almagro et al, 2002; Groenewegen, Schols & Wouters, 2003; Kim, Clark & Camargo, 2006; Piquet et al, 2013; Ho et al, 2014). Male gender is also associated with increased mortality, although not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…One-year mortality in COPD patients is 4.3–43%, depending on the subgroup examined (Table 1) (Connors et al, 1996; Almagro et al, 2002; Groenewegen, Schols & Wouters, 2003; Kim, Clark & Camargo, 2006; Coleta et al, 2008; Fan et al, 2007; Gershon et al, 2010; Piquet et al, 2013; Ho et al, 2014; Müllerova et al, 2015). Mortality shows a downward trend in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital mortality for COPD varies from between < 10% and 60%, based on the severity level of the population studied 50 and the 1-year rate is about one in four (28% for Canadian discharge data between 2001 and 2004; 51 and 25% within 1 year of admission for the first acute exacerbation between 2005 and 2007 in Taiwan). 52 Our mortality rate within 1 year of an index COPD admission was 24%.…”
Section: Comparison With Previous Workmentioning
confidence: 71%
“…Unlike osteoporosis, in which the most common cause of mortality is fractures, 26,27 mortality related to COPD is multifactorial and includes exacerbations of COPD, respiratory infections, and worsening of other medical illnesses that are commonly comorbid with COPD, including coronary artery disease, heart failure, hypertension, and stroke. 25,28,29 Literature in nondepressed patients with COPD has shown that advanced age, overall medical burden, exercise tolerance, daily physical activity, home oxygen therapy use or noninvasive mechanical ventilation, altered mental status, and use of inspiratory accessory muscles or paradoxical breathing are associated with mortality on follow-up. 25,[30][31][32] These findings suggest that overall debility predicts mortality in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…25,28,29 Literature in nondepressed patients with COPD has shown that advanced age, overall medical burden, exercise tolerance, daily physical activity, home oxygen therapy use or noninvasive mechanical ventilation, altered mental status, and use of inspiratory accessory muscles or paradoxical breathing are associated with mortality on follow-up. 25,[30][31][32] These findings suggest that overall debility predicts mortality in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%